2021
DOI: 10.1108/k-04-2021-0336
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the differential effects of pride and guilt along with values on green intention through environmental concern and attitude

Abstract: PurposeIn response to scholarly calls, the study aims to extend and magnify the existing understanding by unravelling the differential impact of anticipated emotions on green practice adoption intention through a proposed model by integrating anticipated pride and guilt in the same continuum along with values (altruistic, biospheric and egoistic) on an employee's attitude.Design/methodology/approachA self-administered questionnaire was used to collect data randomly from 307 employees and middle-level executive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 157 publications
(293 reference statements)
4
7
0
Order By: Relevance
“…Problems might occur when certain creators decide to create certain contents that actually do not match their field of expertise, in which such a step could lead people to believe that all of the information provided within the video is questionable, which, other than lowering people’s assessment of the credibility of the creator, can also lead viewers to find another similar video that was created by a more trustworthy (and credible) individual. Moreover, this result also matched the results obtained by previous studies which also found the significance of attitude in determining people’s intention and actual behavior (Venciute et al , 2023; Doung, 2023; Garcia et al , 2022; Keshavarz et al , 2021; Mukherjee and Chandra, 2022; Park et al , 2022).…”
Section: Resultssupporting
confidence: 91%
“…Problems might occur when certain creators decide to create certain contents that actually do not match their field of expertise, in which such a step could lead people to believe that all of the information provided within the video is questionable, which, other than lowering people’s assessment of the credibility of the creator, can also lead viewers to find another similar video that was created by a more trustworthy (and credible) individual. Moreover, this result also matched the results obtained by previous studies which also found the significance of attitude in determining people’s intention and actual behavior (Venciute et al , 2023; Doung, 2023; Garcia et al , 2022; Keshavarz et al , 2021; Mukherjee and Chandra, 2022; Park et al , 2022).…”
Section: Resultssupporting
confidence: 91%
“…Employees who are committed and qualified are usually always reliable and will devote their abilities to the maximum. The previous study by Mukherjee and Chandra (2021) showed that expected guilt influences individual cognition and future ecological decision-making through improved attitudes and increased interest in the environment, while pride only affects attitudes. Meanwhile, research by Bhatnagar and Aggarwal (2020) concluded that eco-friendly initiatives from employees, increasing psychological capital, and reducing isolation need to be carried out.…”
Section: Eco-friendly Commitmentmentioning
confidence: 96%
“…, 2017; Marquis and Qiao, 2020). “Behavioural channeling” occurs when individuals see what they want to see and hear what they want to hear, thus enabling them to inject their own values into their choices (Marquis and Qiao, 2020; Mukherjee and Chandra, 2021). This is, in part, due to individuals making decisions that are clearly in line with their preferences.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Ideological imprinting shapes decisions to adopt (or resist) certain practices or policies through two interwoven mechanisms: behavior channeling and perceptual filtering (England, 1967;Gupta et al, 2017;Marquis and Qiao, 2020). "Behavioural channeling" occurs when individuals see what they want to see and hear what they want to hear, thus enabling them to inject their own values into their choices (Marquis and Qiao, 2020;Mukherjee and Chandra, 2021). This is, in part, due to individuals making decisions that are clearly in line with their preferences.…”
Section: Communist Ceos and Corporate Environmental Responsibilitymentioning
confidence: 99%